GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 632941152 species occurrences available in GBIF matching the query: HasCoordinate: true HasGeospatialIssue: false. The dataset includes 632941152 records from 13538 constituent datasets: 21447 records from Herbarium de Geo. B. Hinton, México. 69 records from Mönchspark. 977 records from Gurgltal (Tarrenz). 50 records from Unser Schulhof. 34516 records from LSUMZ Mammals Collection. 1514 records from Gemeinde Sursee. 188 records from Ökostation (Freiburg). 114 records from Liether Kalkgrube. 3989 records from SOUTHERN OCEAN ISOPODA. 281250 records from Quadrige. 24977 records from Mycology herbarium, Tromsø Museum. 1795 records from Collection Arachnida - SNSD. 104579 records from Entomological collections, UiB. 108594 records from UMMZ Mammal Collection. 12 records from Collection Bryozoa - ZIM Hamburg. 127 records from Birdrace_Schräge_Vögel-Herford. 115264 records from UAM Mammal Collection (Arctos). 58 records from Schulgelände Städtisches Gymnasium. 2 records from Kirchenforst. 85 records from Schulgelände IGS Kaufungen. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 311 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 6 records from Wiese. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 19 records from Occurrence of mammalia relicts at site Gröbern. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 145 records from Whale log - observations from ANARE voyages. 852 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 8780 records from Artròpodes d'Andorra. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 1831 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1115906 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 44 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 5139 records from Herp Collection. 3 records from Nannofossil abundance of Hole 94-609A. 498 records from The Danish Newt Collection. 17618 records from BioGIS - Mammals - INPA database. 5050 records from Ontario BioBlitz Species Records. 1 records from Waldtag in und um Seelingstädt. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 11 records from Zoobenthos in surface sediments off Cape Lucul. 71 records from (Data S1) Palynology of ODP Site 113-696. 3 records from A new species of Eigenmannia Jordan and Evermann (Gymnotiformes: Sternopygidae) from the upper rio Paraguai basin. 95 records from BIRDRACE BiBi. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 133 records from Schellenberg A. 1936. The fishery grounds near Alexandria. 10. Amphipoda Benthonica. Notes and memoirs no 11. 13 records from FND "Weißer Berg" Leißling. 126 records from Total foraminifera counts from M35/1_MSN1050. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 3 records from Nannofossil abundance of Hole 31-301. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 2182 records from Ibaraki Nature Museum, Mollusk collection. 15389 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 274 records from Foraminifera abundance of sediment core BM1958.631. 3 records from Analyses of the recent components of sediment core PS1215-2. 156 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 16 records from Coccolith counts of multinet M32/5_MSN986. 496 records from 2000-2003 RBWM WHS Surveys. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 3953 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 102 records from Range table from planktonic foraminifers in ODP Hole 169-1035D. 1404 records from Arachnologie - SMNG. 49 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 209 records from Relative abundance of coccosphere-units at site GIK23414. 451 records from Nannofossil abundance of Hole 15-148. 21 records from Nannofossil abundance of Hole 6-55. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 558 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 1972 records from (Figure 6) Distribution chart of benthic foraminifers in ODP Site 126-792. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 12832 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 306 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 5 records from Two new endemic species of Epictia Gray, 1845 (Serpentes: Leptotyphlopidae) from Northern Peru. 40825 records from Ditsong National Museum of Natural History Collection: 1805-2008. 20 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 29 records from Klimaoasen in Köln. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 6 records from Sediment properties of core PLG93_BCORE1. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 1691 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 13003 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 66709 records from United States National Plant Germplasm System Collection. 780 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 164 records from Planktic foraminifera abundance of Hole 22-215. 126 records from Planktic foraminifera abundance of Hole 32-305. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 2260 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 36506 records from Plant Specimens of Kurashiki Museum of Natural History. 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 3 records from Microfossil abundance of Hole 50-415. 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 3 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 73 records from VFD-HH/SH: Pferdweide Lammert. 18 records from Meiofauna abundance in sediment core 13368-015. 40665 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 14637 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 16695 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 880 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 30 records from Benthic foraminifera abundance of Hole 42-379A. 53 records from Planktic foraminifera abundance of Hole 29-281A. 2 records from Ice Amphipods Canada Basin. 30 records from Nannofossil abundance of Hole 8-71. 1 records from A NEW SPECIES OF DRY FOLIAGE MIMICKING Eriovixia ARCHER, 1951 FROM CENTRAL WESTERN GHATS, INDIA (ARANEAE: ARANEIDAE). 135 records from Total foraminifera counts of multinet M21/3_MSN688. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 62487 records from Ornitho.eus. 2895 records from Estudio de la fauna edáfica en una selva baja inundable de la Reserva de la biósfera de Sian Ka'an Quintana Roo. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 3204 records from Faunal Inventory of Morysin Nature Reserve. 11 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 61 records from Fürstenberger Ralley Teil 3. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 646 records from Engraulidae-Clupeidae. Report on the Danish Oceanographical Expeditions 1908-1910 to the Mediterranean and adjacent seas. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 68 records from Planktic foraminifera abundance of Hole 22-213. 26 records from Planktic foraminifera abundance of Hole 20-200A. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 2 records from Abundance of benthos infauna at station GIK23025-2. 17 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 1849 records from National Trust - Heigham Holmes species data held by The National Trust. 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 4 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 176729 records from CAS Entomology (ENT). 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 2 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 627 records from Inventario forestal en bosques dominados por encino (Quercus Fagaceae) en la Sierra de Manantlán, Jalisco-Colima, México: Descripción de los patrones de respuesta al medio físico y biológico. 101 records from MVZ Mammal Observations (Arctos). 3 records from Contribution to the knowledge of Neoperla (Plecoptera: Perlidae) from Hainan Province of China. 9 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 2 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 3512 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 83 records from Planktic foraminifera abundance of Hole 14-135. 10 records from Three new species and redescription of the type species of Soesilarishius Makhan, 2007 (Araneae: Salticidae: Euophryini). 18 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 117 records from Wassermann. 105 records from BIRDRACE coesfelder_vogelkundler. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 87 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 374 records from Diversidad y distribución del género Tripsacum (Poaceae: Tripsacinae) en México. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 132192 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 921 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 110 records from Abundance of planktic foraminifera at CTD station M39/4_366CTD-22. 22 records from Phytoplankton abundance at bottle station GOM6/1. 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 308 records from Planktic foraminifera counts of sediment core V19-178. 2357 records from Foraminifera abundance of Hole 17-167. 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 10 records from Benthic macrofauna abundance of sediment core 13078-017. 23 records from Contribution to the knowledge of the genus Singilis Rambur, 1837 of Africa (Coleoptera: Carabidae: Lebiini). Part IV. 14473 records from Ontario Breeding Bird Atlas 1981-1985. 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 9402 records from MEXU/Plantas Vasculares. 46 records from An der Ohm, (Wettsaasen). 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 1114 records from MEXU/Tipos de plantas vasculares. 5233 records from (Appendix A) Stable carbon and oxygen isotopes and paleoproductivity reconstructions for the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 82641 records from Vascular Plants, Observations, Oslo (O). 257 records from Kernberge und Umgebung (Jena). 28 records from Occurrence of mammalia relicts at site Climauti II. 1351 records from Neogene palynomorpha from site 93-603, part 1. 1 records from Planktic foraminifera abundance of Hole 8-72. 163 records from Planktic foraminifera abundance of Hole 32-313. 525 records from Planktic foraminifera abundance of Hole 94-609. 82 records from Filogeografía y recursos genéticos de las vainillas de México. 1494 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 2 records from The Genus Criodion (Audinet-Serville, 1833) (Coleoptera, Cerambycidae): First Record for Panama. 4872 records from Abundance and diversity of the Amphipoda (Crustacea) from the Greenlandic shelf. 146926 records from Etapa final de la captura y catalogación del Herbario del Instituto de Ecología, AC, Centro Regional del Bajío. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 1. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 501 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 219242 records from R. L. McGregor Herbarium Vascular Plants Collection. 70 records from Exotic terrestrial flatworms, Macquarie Island. 12 records from Abundance of epibenthic echinoderms at seafloor photography station M21/5_317. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 1664 records from ZUEC-AVE - Coleção de Aves do Museu de Zoologia da UNICAMP. 1545 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 748 records from Moluscos Marinhos de Augusto Nobre. 388 records from Mooswald (Freiburg). 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 1 records from Results of palynological analysis of Hole 302-M0004C. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 3711 records from Florida Keys Reef Visual Census 2004. 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 9 records from Nannofossil abundance of Hole 60-455. 81 records from Colección de Referencia de Poliquetos del Museo de Ciencias de la Universidad El Bosque. 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 116639 records from The digitization of plant specimens of NTU. 5 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 161917 records from Field Museum of Natural History (Zoology) Mammal Collection. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 101 records from Birdrace-Herford-Birder-Herford. 15 records from AKG-Bensheim. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 212578 records from MVZ Mammal Collection (Arctos). 1994 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 1 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 35 records from Gym Freyung. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 26 records from Polychaeta Orbiniidae from Antarctica, the Southern Ocean, the Abyssal Pacific Ocean, and off South America. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 2997 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 13128 records from Mycology herbarium, NTNU University Museum. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 5241 records from Nordic Genetic Resources. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 1056 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 4 records from Redescriptions and new host records of chewing lice of the genus Ricinus (Phthiraptera: Ricinidae) from the Neotropical Region. 66 records from Foraminifera abundance of Hole 55-432A. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 3 records from Collection Xiphosura SMF. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 168 records from Weidenhüttendorf an der Würm (München). 61 records from Plant specimens of Hokkaido University Museum. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 899 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 3191 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 20 records from Mikroorganismen. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 2563453 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 939 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 22 records from Nannofossil abundance of Hole 9-83A. 6992 records from ZUEC-LEP - Coleção de Lepidoptera do Museu de Zoologia da UNICAMP. 17344 records from Base de datos del Herbario CIQR de El Colegio de la Frontera Sur, unidad Chetumal. 48 records from Wahner Heide LK 12 Biologie. 2233 records from Chrysomelidae of Poland. 133 records from Total foraminifera counts of multinet PO247/2_MSN1381. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 115 records from Nannofossil abundance of Hole 29-279A. 5424 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 1 records from Fiocruz/COLPROT - Coleção de Protozoários. 36301 records from Pelagic Fish Observations 1968-1999. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 700 records from Estudios previos justificativos para la declaratoria de áreas naturales protegidas en Tamaulipas. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 21 records from Nannofossil abundance of Hole 24-232A. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 68 records from paleovertebrados. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 6163 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 20146 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 97 records from LauWi. 114 records from BIRDRACE VIE will rock you!. 72 records from Faunal assemblage of sediment core TR149-35. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 56 records from Nannofossil abundance of Hole 94-607. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 271 records from Planktic foraminifera counts of sediment core RC11-147. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 64 records from Feuchtbiotop Weidenkaule. 1723 records from KTU Pinophyta. 7070275 records from Great Backyard Bird Count. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 30659 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 5733 records from Small Mammal Research Database. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 32761 records from National fish tag database. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 125 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 1728 records from CASES: The pre-winter assemblages of southeastern Beaufort Sea. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 19 records from Nannofossil abundance of Hole 31-298. 672 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 106 records from Anfibios y reptiles de la sierra de Cuatro Venados, Oaxaca, México. 48479 records from IMOS - AusCPR: Zooplankton Abundance. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 30890 records from MEXU/Asteraceae. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 107 records from Planktic foraminifera abundance of Hole 18-180. 77 records from Total foraminifera counts from M35/1_MSN1075. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 5 records from Analyses of the recent components of sediment core PS1400-4. 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 2787 records from Algae, Specimens, Agder naturmuseum (KMN). 416866 records from Entomology, Natural History Museum, University of Oslo. 43 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV30_1. 99 records from Planktic foraminifera abundance of Hole 94-610E. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 241 records from Planktic foraminifera abundance of Hole 67-499B. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 353 records from Colección de Entomología - Arthropoda. 160 records from Wirbach-Taubental (Bad Blankenburg). 318 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 33 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 86 records from Fliegenhaupt Marksuhl. 24402 records from Ibaraki Nature Museum, Arthropoda collection. 121 records from Dorset Argiope - NBN South West Pilot Project Case Studies. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 2610 records from Flora genérica de las gramíneas del estado de Tlaxcala. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 32 records from Billards A. 1936. Les fonds de peches pres d Alexandrie. VI Hydroidea. Notes et memoires No 24. 107 records from BIRDRACE Herford Birders. 1 records from Taxonomic revision of the Malaysian Idiocerinae (Hemiptera: Cicadellidae), with description of new taxa. 1 records from Pollen and spore abundance of Hole 42-379A. 356 records from Biotope in Rheine - Aktion 350. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 52 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 32 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 1183 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 3761 records from Mountain Invasion Research Network (MIREN) survey. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 35266 records from Kathryn Kalmbach Herbarium. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 31 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cadder Wilderness SSSI. 4826 records from Vascular Plants Collection of National Museum of Nature and Science. 10482 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 564 records from V. N. Karazin National University. 76 records from Colección de Entomopatógenos de México (CNRCB). 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 718 records from Zukünftiges NSG Höftland/Bockholmwik. 6987 records from National Trust - Ickworth species data held by The National Trust.. 24 records from Ficha de Sonora aemula. 61226 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 12026 records from Arizona State University Amphibian and Reptile Collection. 10454 records from The Erysiphales Collection at the Botanische Staatssammlung München. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 406 records from Harpactus Shuckard. 90 records from Schulhof Bühlschule Giengen. 48 records from Freiheitsring (Frechen). 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 5 records from Two new species of Huascaromusca Townsend from Colombia, and a new combination for Giovanella carvalhoi (Diptera: Mesembrinellidae). 145180 records from Bernice P. Bishop Museum. 827 records from ZFMK Sound Archive. 23 records from Coleção de Ascidiacea do Museu Nacional - UFRJ. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 22 records from Sediment properties of core PLG95B_06BOXG. 2022 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 131 records from Unser Schulhof - eine Apotheke. 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 305 records from Cuarenta y ocho especies de la flora de Chiapas incluidas en el PROY-NOM-059-ECOL-2000. 2 records from Two new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 170 records from Thistles and numbers of observed invertebrates, fungi and damage types. 8 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 11920 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 57 records from Nannofossil abundance in sediment core PS1311-4. 241 records from Sponges of the Guyana Shelf. 302 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 3 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 84521 records from BioGIS - Vascular plants - INPA database. 47 records from Schulgelände Ceciliengymnasium. 186 records from Total foraminifera counts of multinet M21/1_MSN604. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 774 records from Planktic foraminifera abundance of Hole 80-549A. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 18 records from Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America. 77 records from Inhaltsstoffe_Blattmischproben_2008. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 1 records from Description of a new species of Lutosa Walker, 1869 (Orthoptera: Anostostomatidae: Lutosinae) from the Brazilian Atlantic Forest, with biological and behavioral information. 6 records from UWYMV Herpetology Collection (Arctos). 107 records from 1st Austrian Birdrace (Wien). 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 683 records from Lama Forest reserve Inventory, South Benin. Data published in the framework of JRS Benin project. 3 records from Systematics of a small Gehyra (Squamata: Gekkonidae) from the Einasleigh Uplands, Queensland: description of a new range restricted species. 487 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 6049 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 39385 records from SAEON: Historical Research Survey Database (1897-1949). 48 records from Trockenrasen bei Dörndorf. 103 records from BIRDRACE Die Otzberger. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 315 records from Planktic foraminifera counts of sediment core RC17-69. 24 records from Distribución, abundancia, estructura poblacional y potencial reproductor de Zamia furfuracea L.. 32 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 84 records from BIRDRACE Birding for Nature. 23 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5136-1. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 6 records from Nannofossil abundance of Hole 7-63. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 7 records from Abundance of nematoda in sediment profile M3/1_029 from the Iberian deep sea basin (Table 5). 70 records from Parkuntersuchung Weißer See. 94 records from Coccolith counts of multinet SO119_MSN1298. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 76 records from Coccoliths in sediment core PS1533-3. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 334 records from Listado florístico y etnobotánico de las plantas medicinales de los huicholes del río Chapalagana, Jalisco y del Nayar, Nayarit. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 8858 records from (Appendix 2a) Foraminiferal analyses of research borehole Sonder Vium. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 2 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 25 records from Benthic foraminifera abundance of Hole 1-4. 7720 records from Chondrichthyans Of Ireland. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 1061 records from Antarctic Biodiversity Studies 2006 (Ross Sea, Scott Island, and Balleny Islands) (TAN0602). 57 records from Garten in Schmölln. 231 records from Gunma Museum of Natural History, Fish Specimen. 113 records from Collection Hydrozoa - ZMB. 566 records from (Appendix A1) Distribution of benthic foraminifera in ODP Site 184-1143. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 40 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 13750 records from Impetus - Herbarium Hamburgense. 154 records from Planktic foraminifera distribution of sediment core TRI171-27. 97 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 1 records from Planktic foraminifera abundance of Hole 54-420A. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 1028826 records from SEAMAP - marine mammals, birds and turtles. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 302 records from Stadtpark Sulzbach-Rosenberg. 778 records from Planktic foraminifera abundance of Hole 40-362. 2937 records from Homoptera. 564 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 28256 records from Bosque Mesófilo de Montaña de México. 2 records from New data on the rare Afrotropical scarab beetles Orphnus drumonti Frolov and Delopleurus naviauxi Frolov et Cambefort (Coleoptera, Scarabaeidae, Orphninae and Scarabaeinae). 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 26 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 1200 records from Monocotyledonous Geophytes of Fergana Valley. 1512 records from tree climbing bryophytes & lichens at tree base and crown with traits. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 22 records from Cryptic diversity within the narrowly endemic Lerista wilkinsi group of north Queensland—two new species (Reptilia: Scincidae). 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 588 records from Relative abundance of ostracods in sediment core Lz1120. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 181 records from Collection Crustacea ZMG. 1130 records from Ostracoda in sediment core PS51/154-11. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 65908 records from West African Vegetation Database. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 310 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 2471 records from Diversidad fúngica en planicies del desierto central sonorense y centro del desierto chihuahuense. 13 records from Two new species of Stenaelurillus Simon, 1886 from India (Araneae: Salticidae: Aelurillina). 7 records from Three new Scandinavian species of Culicoides (Culicoides): C. boyi sp. nov., C. selandicus sp. nov. and C. kalix sp. nov. (Diptera: Ceratopogonidae). 6056 records from Lichens of Knyszyn Forest. 11 records from Biology and Ecology of Cryopelagic Amphipods from Arctic Sea Ice Collected near Franz Josef Land in the summer of 1994. 1582352 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 535 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 593 records from Collection Crustacea - KAUMM. 1 records from Two new species of Diastatotropis Lacordaire (Coleoptera: Anthribidae) from east Madagascar with a key to species of the genus. 93 records from Distribución actual, estatus poblacional y evaluación del estatus de protección del pavo ocelado (Agriocharis ocellata). 74 records from SuLaMa reptile monitoring. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 119 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1 records from A revision of the genus Lepidobrya Womersley (Collembola: Entomobryidae) based on morphology and sequence data of the genotype. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 10269 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 12 records from Abundance of radiolaria at station LV28-40-2. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 1 records from Hausgarten. 14 records from Benthic macrofauna abundance of sediment core 12930-093. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 320 records from Myxomycetes collection of the University of Eastern Finland. 441 records from Pollen analysis of surface samples from Germany and Austria. 1532 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 869 records from Lepidoptera Observations from New Zealand by Donald Hobern. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 88 records from Total foraminifera counts of multinet SO118_MSN1265. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 12 records from Abundance of radiolaria at station LV28-44-1. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 4 records from Synonymy and problematic species of Eiconaxius Spence Bate, 1888, with descriptions of new species (Crustacea: Decapoda: Axiidea: Axiidae). 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 3 records from CNIN/Mantodea. 175 records from INSECT COLLECTION. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 93 records from Südwestlich der Parkwiesen. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 2 records from Benthic foraminifera abundance of Hole 42-376. 62015 records from MMNS Ichthyology Collection. 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 19336 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 296 records from DJH. 2000 records from (Table A2) Sea surface temperature reconstruction of DSDP Site 94-607 in the North Atlantic. 201 records from Mammals in MZNA-VERT: project CAS. 17 records from Study on Tychini of Balkan Peninsula (Coleoptera, Staphylinidae, Pselaphinae). 60071 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 2 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 81 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 2839 records from Rocky Shore Macroalgae. 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 6738 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 7104 records from Museu Paraense Emílio Goeldi - Diptera Collection. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 1 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 256 records from BIRDRACE Upupa epöpse. 6 records from Nannofossil abundance of Hole 55-430B. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 13639 records from Senckenberg - CeDAMar Resource. 7795 records from Hymenoptera collection, Natural History Museum, University of Oslo. 10 records from Laccomimus xikrin sp. nov. and new records of other species of Laccomimus Toledo & Michat, 2015 (Coleoptera: Dytiscidae: Laccophilinae) from Brazil. 38 records from A new species of snail-case caddisflies (Trichoptera: Helicopsychidae) and new records of caddisflies from Chapada Diamantina, Bahia, Brazil. 2029 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 28 records from Seasearch Crawfish, Palinurus elephas, Surveys. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 71586 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 2846 records from Coleoptera, NEF. 44 records from Flora und Fauna in unserer Kita. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 233 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 103322 records from Invertebrates Collection of the Swedish Museum of Natural History. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 23879 records from svalbardflora.no. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 145 records from privater Garten. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 66 records from Foraminifera species abundances from tow TT007_10-MOC20. 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 9 records from Microzooplankton abundance and biomass at station TT043_9-1. 599 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 27 records from Coleção de Nemertea do Museu Nacional - UFRJ. 49637 records from Monitoring data from the federal state Hesse (Germany). 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 909 records from Dinámica poblacional de la tortuga de carey (Eretmochelys imbricata) en su área de forraje. Río Lagartos, Yucatán. 5 records from Streuobstwiese (Mittelgasse 4). 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 53 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 54578 records from Fish Specimens. 177 records from Donauinsel des BN bei Entau. 50 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 3 records from Antarctic Arrow worms. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 2723 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 9614 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-120BX. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 216 records from Monitoreo biológico en la cuenca Dagua - Subcuenca La Guinea ARA - RARE - CVC – Asociación Calidris. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 961 records from Fish monitoring data in Lake Kasumigaura. 38984 records from Herbarium (UNA). 114 records from BIRDRACE Di-Bi-Di-Birder. 262 records from (Appendix 6) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD95-2041. 27 records from Zwickau- Schwanenteich. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 21 records from Meiofauna abundance in sediment core 13077-006. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 3 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 92 records from Plasm bearing foraminifera counts of multinet M26/1_MSN843. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 2991 records from Millenium Seedbank (MSB). 16 records from Dinoflagellate cysts of surface sediments. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 144 records from BIRDRACE Punkbirder Helgoland. 27 records from (Table 12) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-666A. 3163 records from Biodiversidad de Datura (Solanaceae) en México. 9721 records from Birds of Ireland. 679 records from Results of palynological analysis of Hole 302-M0004A. 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 49 records from Collection Thysanoptera SMF. 482 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 1 records from A review of the genus Spiropagurus Stimpson, 1858 (Crustacea: Decapoda: Paguridae) from the China seas. 88 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 1417 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 2268 records from (Table 1) Distribution of Cretaceous-Tertiary benthic foraminifers in ODP Hole 129-802A. 279 records from Planktic foraminifera abundance of Hole 11-98. 91 records from Benthic foraminifera abundance of Hole 84-569A. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 2088 records from Benthic foraminifera of sediment core MD99-2286. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 117 records from Muskox Abundance. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 96 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 494248 records from BLS Mapping Scheme dataset, 1750-2009. 36384 records from Inventaire National du Patrimoine Naturel : Amphibiens et Reptiles de France (Enquête 1). 5 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 11 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 5242 records from SANBI: DNA Banking(1987-2011). 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 17329 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 4 records from Dinámica poblacional de Mammillaria crucigera y Neobuxbaumia macrocephala en la región de Tehuacán-Cuicatlán. 4 records from Colección de Referencia de Reptiles del Museo de Ciencias de la Universidad El Bosque. 492 records from Verneplan Hjerkinn karplanter. 3710 records from Araneae_Raw1. 5 records from Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan. 6660 records from Weevils of the Tatra Mts.. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 2 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 454 records from Collection des Mollusques (BOUM). 13624 records from Mammal collection, Natural History Museum, University of Oslo. 153 records from Selztal bei Friesenheim. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 122 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 24 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 214 records from Binsenwiesen. 87 records from Klütwald. 18 records from Landschaftsschutzgebiet Buchhorst2. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 347 records from (Table 4) Standing stock values of important species in surface sediments. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 25 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_8-CTD93. 100 records from Birdrace-Meister_der_Herzen-Kleve. 45 records from Nannofossil abundance of Hole 28-265. 4 records from Estimated plankton abundance at station PS63/064-6. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 394 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 362 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 120714 records from Arizona State University Lichen Collection. 57 records from Occurrence of mammalia relicts at site Moladova V. 1 records from Planktic foraminifera abundance of Hole 8-73. 1042 records from Planktic foraminifera abundance of Hole 37-333. 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 194 records from Collection Cnidaria - ZMB. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 246 records from Benthic foraminifera abundance of Hole 73-524. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 13329 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 8 records from Pollen and spore abundance of Hole 42-380. 121008 records from Mycology herbarium, Oslo (O). 19741 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 10930 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 31499 records from MSB Bird Collection (Arctos). 4511 records from Elaboración del banco de datos de las colecciones del Museo de Zoología-CIQRO. 11 records from Nannofossil abundance of Hole 6-56B. 32112 records from SBMNH Vertebrate Zoology. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 56741 records from Insect Collection of Taiwan Forestry Research Institute. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 764 records from BioGIS - Fish - INPA database. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 1563 records from Mid Ulster Hare Surveys 2012-2015. 29114 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 44 records from Total foraminifera counts of multinet M21/4_MSN721. 921 records from Planktic foraminifera counts of sediment core RC14-37. 14602 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 4 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 1165 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 194 records from Colección Herpetológica de la Patagonia. 188215 records from NINA insect database. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 341 records from Inventario y monitoreo de anfibios y mariposas en la Reserva de Calakmul, Campeche. 16998 records from Modern foraminifera in the New Zealand EEZ. 8 records from Krittenhorster Wald (Ostkilver). 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 3039 records from Flora marina (Clorophyta, Phaeophyta, Rodophyta) y fauna conspicua (Echinodermata, Mollusca, Polychaeta) del Complejo Insular Espíritu Santo-Cerralvo-San José en BCS, México. 763 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 1182 records from Registros faunísticos de invertebrados marinos en el SE del Golfo de California. 102 records from Liste des plantes médicinales utilisées dans la préfecture de Labé et observées sur le terrain.. 276 records from Planktic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 144 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4). 129 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 269 records from 3. Tag der Artenvielfalt Hockenheim. 3 records from A new species of the genus Paramesotriton (Caudata: Salamandridae) from Fujian, southeastern China. 1 records from An extraordinary new genus and species of spider wasps (Insecta: Hymenoptera: Pompilidae) from Southeast Asia. 1379 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 152925 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 7468 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 994 records from (Table 6) Quaternary planktonic foraminifers at DSDP Site 65-483. 471 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 180 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres en La Chinantla. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 12 records from Lepidoptera specimen database of Japan. 961 records from Spencer Entomological Museum. 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 3 records from A new species of Neparholaspis (Acari: Parholaspididae) from Russia, with additional information on Neparholaspis evansi Krantz, 1960. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 39 records from On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae). 145 records from Phytoplankton abundance at station CD46_0405C#7. 9572 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 2 records from Nannofossil abundance of Hole 6-49. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 134 records from Myriapoda - SMF. 193 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 76 records from Occurrence of mammalia relicts at site Vindija. 1660 records from Avifauna del Altiplano de San Luis Potosí. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 314 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 86 records from Pollen analysis of sediment core GIK16856-2. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 304538 records from Observational database of Icelandic plants. 4191 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 1212 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 2148 records from Eppingen und Umgebung. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 55 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 456 records from Range table from benthic foraminifers in ODP Hole 144-873A. 11 records from Observation of birds at station PS14/156 along 49° West. 32 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 2713 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 141 records from Schulhof und Anlagensee in Nellingen. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 50 records from Lindesnes. 1 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 5 records from Tuttlinger Tag der Artenvielfalt. 4 records from Nannofossil abundance of Hole 29-281A. 497 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 4 records from A new Eastern Central Atlantic skate Raja parva sp. nov. (Rajoidei: Rajidae) belonging to the Raja miraletus species complex. 310 records from Lepidoptera systematic collection, NTNU University Museum. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 6 records from Planktic foraminifera abundance of Hole 23-226. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 588 records from NHT flora. 17967 records from UPCB - Herbário do Departamento de Botânica. 1474 records from Formación de las colecciones de referencia de aves y mamíferos de la Reserva de la Biosfera de Sian Ka'an, Quintana Roo, México. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 767 records from BioGIS - Bats - Asaf Tsoar database. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 278 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 163 records from Tiere und Pflanzen am Pfannenbach. 81937 records from Natural History Museum, University of Tartu. 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 3 records from Report of Platythomisus octomaculatus (C. L. Koch, 1845) and Platythomisus sudeepi Biswas, 1977 from India (Araneae, Thomisidae). 155970 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 2182 records from Avifauna de la Reserva de la Biosfera La Sepultura, Chiapas. 1 records from Diatom abundance of Hole 95-613. 2114 records from Dry Tortugas Reef Visual Census 2010. 18 records from Planktic foraminifera abundance of Hole 32-310. 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 30 records from Leben auf einer Sturmfläche. 14 records from Nannofossil abundance of Hole 85-573. 405 records from Collection Graptolithina fossil SMF. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 212 records from (Table T4) Planktonic foraminifera abundance of ODP Site 170-1042 sediments. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 78799 records from natagora-earlybirds. 820426 records from Fauna Atlas N.T.. 87 records from Total foraminifera counts of trap L2_92_B49. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 2982 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 5862 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 5327 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 759 records from Planktic foraminifera abundance of Hole 47-398D. 70 records from Planktic foraminifera abundance of Hole 84-569A. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 18 records from Meiofauna abundance in sediment core 13200-012. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 35 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 6594 records from Biodiversidad de los mamíferos en el Estado de Michoacán. 878 records from Planktic foraminifera abundance of Hole 84-568. 1 records from Abundance of benthos infauna at station GIK23004-3. 661 records from Targeting a portion of central European spider diversity for permanent preservation. 1050 records from ZUEC-COL - Coleção de Coleoptera do Museu de Zoologia da UNICAMP. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 316 records from Planktic foraminifera counts of sediment core V14-101. 3 records from Analyses of the recent components of sediment core PS1215-2. 12 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 244 records from WildesMoor bei Schwabstedt. 1496 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 9042 records from Northern Biodiversity Program Coleoptera (2010-2011). 1589 records from Global caridean shrimp fauna. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 28 records from Nannofossil abundance of Hole 26-253. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 12697 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 190 records from Foraminifera abundance of sediment core MD81-LC07. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 73 records from Planktic foraminifera abundance of Hole 2-11. 692 records from Planktic foraminifera abundance of Hole 40-360. 94 records from Planktic foraminifera abundance of Hole 80-550. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 32 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 347639 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Trawl. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 17 records from Coleção de Brachiopoda do Museu Nacional - UFRJ. 24 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 48913 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 142 records from Kinderbauernhof Pinke-Panke. 940 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 45 records from Parcela Permanente en el Pantano Martos. 96 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 54 records from Wiese am Unterbecken. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 556 records from Distribution ashore and breeding places of southern elephant seals. 27 records from Benthic foraminifera abundance of Hole 34-320A. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 10577 records from Colección de Sifonápteros del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 208 records from Thistles damage. 7 records from Additions to the myxobiota of the Åland Islands. 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 1 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 3299 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 4445 records from Marie-Victorin Herbarium (MT) - Bryophytes. 11266 records from Sightings Map of Invasive Plants in Portugal. 753 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 1374 records from A nest-site survey of Barn swallow at railroad stations in the Kinki District,south-central Japan. 72295 records from NINA Vanndata øvrige arter. 342 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 166 records from Simpson´s diversity of Coleoptera and Heteroptera. 23215 records from rmca-albertine-rift-butterflies. 99 records from Düne am Ulvenberg (Darmstadt). 13 records from Tag der Artenvielfalt am Bruckenwasen. 29 records from Further contribution to the knowledge of Georgian species of the Carabus Linnaeus, 1758 subgenus Neoplectes Reitter, 1885, with description of a new subspecies of C. titarenkoi Zamotajlov & Fominykh, 2014 (Coleoptera: Carabidae: Carabini). 20 records from Motzener Tonsee. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 2 records from Nannofossil abundance of Hole 74-526. 535 records from Benthic foraminifera abundance of Hole 73-522. 2117 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 7685 records from European riparian ground beetles. 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 70615 records from Marsh Monitoring Program - Birds. 520 records from Planktic foraminifera abundance of Hole 39-357. 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 68 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 4224 records from Actualización de la colección ictiológica de Ecosur-Chetumal. 161 records from BIRDRACE Nord-Seh-Team. 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 82 records from Foraminifera species abundances from tow TT011_5-MOC63. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 4 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 554 records from SNH Invertebrate Site Condition Monitoring 2013/14: Abernethy Forest SSSI. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 1432 records from Quaternary benthic foraminifera abundance of Hole 95-612. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 359 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 264743 records from ArtenFinder. 18 records from The water mite family Aturidae Thor (Acari: Hydrachnidia) from Ghana, with the description of twelve new species. 12 records from Distribution of meiobenthos in sediment core M23_134 of the northeastern Atlantic (Table 1). 19515 records from MfN - Fossil invertebrates Ia. 104 records from Ross Sea Pycnogonids. 131 records from Artenvielfalt auf dem Schulgelände. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 144 records from Total foraminifera counts of multinet M21/2_MSN640. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 1 records from Microplankton counts and carbon biomass at station TT007_15-CTD160. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 26 records from Ostracoda abundance of Hole 13-132. 3 records from Nannofossil abundance of Hole 51-417D. 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 44 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 21146 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 161 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 988 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 208 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 2653 records from Florida Keys Reef Visual Census 2005. 102 records from Ostracod abundance in sediment core Lz1120. 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 5110 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 2041 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 8547 records from Individual Sightings. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 1 records from Orthotrichum dentatum T. Kiebacher & Lüth sp. nov. (Orthotrichaceae). 36 records from Nannofossil abundance of Hole 14-141. 151 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 52865 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 43638 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 76911 records from University of British Columbia Herbarium (UBC) - Algae Collection. 610 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 52 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 221 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 5 records from Colección de Referencia de Platelmintos del Museo de Ciencias de la Universidad El Bosque. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 1346 records from Percentages of planktonic foraminifera species in sediment core V25-59. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 92 records from Siliceous microfossil occurrence, Site 177-1094. 25545 records from Formidabel; Belgian Ants Database. 92 records from Flora vascular de los manglares de Marismas Nacionales, estado de Nayarit. 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 31 records from Fundación Miguel Lillo - Colección Invertebrados. 227 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1051 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 772 records from Fishes of the Congo River 2010 Expedition. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 1436 records from Cowan Tetrapod Collection - Herpetology. 29644 records from Phanerogamic Botanical Collections (S). 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 381263 records from University of Florida Vertebrate Paleontology. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 13 records from A new subterranean Iberian Cephennium with unusually modified metatrochanters (Coleoptera, Staphylinidae, Scydmaeninae). 2 records from A second species, and first Central American record, of the phorid fly genus Lenkoa Borgmeier (Diptera: Phoridae). 852 records from flower availability 2008 Hainich. 9948 records from Bees of Canada / Gschwendtner property collection. 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 8 records from Abundance of radiolaria at station LV28-29-1. 3455 records from Las monocotiledóneas mexicanas, una sinopsis florística. Parte II. 155 records from Bergbaufolgelandschaft am Muldestausee. 15 records from Herdengelhoehle taxa and datings. 4516 records from CHAS Mammalogy Collection (Arctos). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 4542 records from Ibaraki Nature Museum, Algae collection. 2141877 records from Biologiezentrum Linz. 84 records from BIRDRACE Vogelscheuchen. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 6 records from Ökosysteme rund um Wedel. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 3297 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 14997 records from iziko South African Museum - Fish Collection (AfrOBIS). 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 2 records from Smear slide analysis of sediment core GeoB7427-2. 16 records from Nannofossil abundance of Hole 47-398B. 29 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 23077 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 66 records from Range table from ostracoda in ODP Hole 151-910D. 922 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 8 records from Occurrence of mammalia relicts at site Wretton. 741 records from Planktic foraminifera abundance of Hole 20-200. 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 8981 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 1 records from Microfossil abundance of Hole 42-378. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 5732 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 777 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 8407 records from NYSM Birds. 1 records from Boraginaceae (Cynoglossum cherangauiense). 458 records from EAN - Herbário Jaime Coelho de Moraes. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 2020 records from Bryophyte collection of Jyväskylä University Museum. 168 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 82736 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 3651 records from Planktic foraminifera abundance of Hole 72-516F. 84943 records from Herbarium of Umeå University (UME). 302 records from Range table from benthic foraminifers in ODP Hole 144-874B. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 585 records from (Tab. 4) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hills. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 4 records from Collection Pantopoda SMF. 16040 records from Naturalis Biodiversity Center (NL) - Porifera. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 75 records from Range table from nannofossils in ODP Hole 199-1220A. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 2 records from Discovery of a new millipede species in northern Vietnam, and the proposal of a new genus, Parariukiaria (Diplopoda, Polydesmida, Xystodesmidae). 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 67 records from Tongrube bei Hettstedt. 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 45 records from Wasser-Lernort Nettemündung. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 102 records from Benthic foraminifera abundance of Hole 42-372. 1525 records from The French Collection of Medicago truncatula. 180 records from Range table from ostracoda in ODP Hole 144-871A. 349 records from Planktic foraminifera counts of sediment core V20-170. 3057 records from Florida Keys Reef Visual Census 2010. 531 records from Expedición Providencia I - INVEMAR. 7 records from Nannofossil abundance of Hole 38-336. 591 records from Planktic foraminifera counts of sediment core V16-25. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 39 records from Red list project inventory, fungi. 5835 records from UPRM Invertebrate Collection. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1443 records from Odonata of the Congo River 2010 expedition. 18353 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 241 records from BIRDRACE RennVögel Münsterland. 112 records from BIRDRACE Gütersloher Gimpel. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 48 records from Diatom assamblage in samples from sediment trap OG5. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 3 records from Sarcodine counts and carbon biomass at station TT011_2-CTD21. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 5133 records from Códigos de barras de la vida en peces y zooplancton de México. 5079 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 9088 records from Flora of Słowiński National Park, Poland. 57 records from Schulgarten Janusz-Korczak-Realschule. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 1 records from Antarctic Marine Amoebae. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 2633 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 777 records from Planktic foraminifera counts of sediment core RC17-108. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 8188 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 11370 records from Distribution of planktic foraminifers of core V22-174. 7684 records from Seed bank grassland. 2227 records from Fundación Miguel Lillo - Colección Ornitológica. 24 records from Occurrence of mammalia relicts at site Overmere. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 44 records from Planktic foraminifera abundance of Hole 19-188. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 2022 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 340 records from Occurrence of mammalia relicts at site Brillenhöhle. 2083 records from Planktic foraminifera abundance of Hole 72-517. 7 records from Range table from planktonic foraminifers in ODP Hole 192-1185B. 209 records from pflanzendiversitaet_2008_sch_zweiter_durchgang. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 14564 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 19 records from Dinoflagellate abundance of Hole 81-553A. 2 records from A new species of the genus Leptobrachium (Anura: Megophryidae) from the Gaoligongshan Mountain Range, China. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 1122 records from ZFMK DORSA. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 498 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 1 records from Abundance of benthos infauna at station GIK23062-2. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 20626 records from BC Coastal Waterbird Survey. 172 records from Foraminifera abundance of Hole 59-448A. 2032 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 26397 records from EWT: African Crane Conservation Programme Sightings. 58 records from ZUEC-AST - Coleção de Asteroidea do Museu de Zoologia da UNICAMP. 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 76 records from Faunal assemblage of sediment core GS7603-10. 171 records from Total foraminifera counts of multinet M42/3_MSN1370. 19 records from Revision and phylogeny of the Caribbean weevil genus Apotomoderes Dejean, 1834 (Coleoptera, Curculionidae, Entiminae). 1 records from Contribution to the knowledge of Chinese Phasmatodea III: Catalogue of the phasmids of Hainan Island, China, with descriptions of one new genus, one new species and two new subspecies and proposals of three new combinations. 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 112 records from Total foraminifera counts of multinet M11/1_MSN526. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 1537 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 108-657A. 116 records from (Table 17) Distribution of planktonic foraminifers in ODP Hole 108-668B. 70467 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 1298 records from Planktic foraminifera abundance of Hole 23-219. 1 records from Two new troglobiotic palpigrades (Palpigradi: Eukoeneniidae) from Brazil. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 96 records from Birdrace-federleser-Herford. 35345 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 15074 records from NBMP Field Survey. 1506 records from Computarización de la Colección de Referencia para Zoología, Arqueozoología y Paleontología del Museo de Historia Natural de la Universidad Autónoma de Baja California Sur. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 169 records from Planktic foraminifera counts at CTD station PS55/051. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 1 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 490 records from flower availability 2007 Schwäbische Alb. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 147 records from NABU-Auerochsenweide. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_236-1. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 175 records from Revisión periódica de Agave victoriae-reginae en el apéndice II de la CITES. 100 records from Birdrace-The_Ringers-Friesland. 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 596 records from Planktic foraminifera counts of sediment core A15-558. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 57 records from Heidesee / Halle. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 438 records from (Table 4) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-709A. 1680 records from Estudio comparativo del zooplancton en dos regiones de México. 40 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 212 records from Nanoplankton abundance at station GeoB2017-1. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 355 records from (Table A3) Semi-quantitative frequency of Globorotalia menardii in core SO164-17-2. 5860 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 3224 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 8787 records from CRI - Herbário Pe. Dr. Raulino Reitz. 38331 records from Botanical Museum, Copenhagen, Mycology Herbarium. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 1 records from Gobiesox lanceolatus, a new species of clingfish (Teleostei: Gobiesocidae) from Los Frailes submarine canyon, Gulf of California, Mexico. 1835 records from ARKO Overvåking kalklindeskog. 1 records from Museu Paraense Emílio Goeldi - Mollusca Collection. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 91 records from BIRDRACE SchrägeVögel. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 294 records from Naturgarten Langenholtensen. 42 records from Foraminifera abundance of Hole 24-236. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 498 records from Dinoflagellate abundance of Hole 94-611C. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 8305 records from Collection Bryozoa SMF. 380 records from UAM Herpetology Collection (Arctos). 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 50703 records from Seasearch Marine Surveys in Ireland. 139 records from Siliceous microfossil occurrence, Site 177-1093. 1147 records from Herpetofauna de la región El Huizache, San Luis Potosí. 12699 records from MVZ Egg and Nest Collection (Arctos). 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 5128 records from Spider Mites Collection of Jean Gutierrez. 16 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 1 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 148 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 14165 records from Entomology at ZMUC, Natural History Musem of Denmark. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 21 records from On the Lathrobium fauna of the Luoxiao Mountains, Central China. 3 records from Blankenfelder See. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 783 records from Phytoplankton abundance in surface water during cruise CD61. 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 21312 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 1488 records from Collection of Occurrence data on mammal species during wildlife census in W Biosphere Reserve in 2013 and 2015. Data mobilized in the framework of the BID-AF2015-0030-SMA project of Isidore Amahowe. 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 140273 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 73 records from AMF colonization in Plantago. 236 records from GENT Lactarius Deliciosi. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 35 records from Nannofossil abundance of Hole 78-543. 6 records from Nannofossil abundance of Hole 6-49. 1997 records from Aves de la cuenca media del río Bogotá. 574 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 6086 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 135 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 115 records from (Table 2a) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Canary upwelling. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 27 records from synthese_Protistdiversity_KG. 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 9 records from Nannofossil abundance of Hole 1-2. 97 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 2390 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 2184 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 1 records from Dinoflagellate abundance of Hole 19-183. 186305 records from KU Museum of Invertebrate Paleontology. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 59304 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 3 records from New records of doryctine wasps (Hymenoptera: Braconidae) from Argentina, with the description of Shawius diiorioi Martínez sp. nov.. 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 753 records from Planktic foraminifera counts of sediment core V28-127. 15425 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 3161 records from Distribution of foraminifera of sediment core ENAM93-21. 19 records from Microplankton data off Mejillones, 2006, Chile. 143 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 36 records from Range table from planktonic foraminifers in ODP Hole 144-877A. 13593 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 15002 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 681 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 12 records from Nannofossil abundance of Hole 20-200. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 29869 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2 y 3. 495 records from Life Science National Tsing Hua University. 1406 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 15 records from Occurrence of mammalia relicts at site Dendermonde. 7 records from Nannofossil abundance of Hole 5-33. 3 records from Planktic foraminifera abundance of Hole 54-424B. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 703 records from Planktic foraminifera counts of sediment core V25-59. 371 records from Planktic foraminifera abundance of Hole 63-470. 176005 records from Mammalogy Collection - Royal Ontario Museum. 66005 records from CAS Ornithology (ORN). 43 records from Schulgelände Thurmair-Gymnasium. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 21 records from Collection Ctenophora SMF. 3 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 8594 records from ColRest_Raw1. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 6 records from Fließgewässeruntersuchung am Haselbach. 65 records from BIRDRACE Federal Birds of Investigation FBI. 16 records from Nannofossil abundance of Hole 9-77B. 730 records from MATRIX project, Budongo fragments birds. 9157 records from BMSM Bailey-Matthews National Shell Museum. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 2441 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 24 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 1101 records from Relative abundance of ostracods in sediment core Co1202. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 84 records from Benthic foraminifera abundance of Hole 84-566C. 38 records from Microfossil abundance of Hole 21-206C. 8100 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 77806 records from Royal Botanic Garden Edinburgh Herbarium (E). 684360 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 13 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America Part I. Genus Scatopsciara Edwards, 1927. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 18703 records from Endemic plants of the Congo basin. 9 records from Maculabatis ambigua sp. nov., a new whipray (Myliobatiformes: Dasyatidae) from the Western Indian Ocean. 95 records from Vielfalt verschiedener Wiesen. 33 records from Schüler erforschen die Helme-Aue. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 262 records from Speothos Venaticus por Guillermo Gil. 5 records from Schulwald Regionale Schule Sprendlingen. 14 records from Nannofossil abundance of Hole 8-72A. 15 records from Microfossil abundance of Hole 59-450. 157035 records from The Himalayan Uplands Plant database (HUP Version 1). 19 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 5238 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 317 records from Planktic foraminifera counts of sediment core RC14-29. 214 records from Fiocruz/COLTRYP - Coleção de Trypanosoma de Mamíferos Silvestres, Domésticos e Vetores. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 621517 records from Museum of Comparative Zoology, Harvard University. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 415 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 807 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 77 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2009. 35384 records from NMSA: Arthropod Collections (1900-2012). 76 records from The Ants of Bulgaria. 2 records from Nannofossil abundance of Hole 29-280A. 149 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 909 records from Computarización de la Colección nacional del phylum Porifera Gerardo Green. 17 records from Hazel Dormouse in Ireland. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 3 records from Nannofossil abundance of Hole 22-212. 3062 records from Mamíferos silvestres de la cuenca del río Mezquital-San Pedro, Durango-Nayarit. 10075 records from Nematoda of Costa Rica (INBio). 55317 records from Local Wildlife Site Surveys Berkshire. 56436 records from Tasmanian Museum and Art Gallery provider for OZCAM. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 85 records from Birdrace-Die_Paradiesvögel-Herford. 300 records from Estudio monográfico de los gasteromicetos del noroeste de Baja California, México. Provincia Californiana. 504 records from Schatzinsel Wangerooge. 248 records from Schulgarten der Volksschule. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 8 records from Nannofossil abundance of Hole 49-409. 129 records from Nannofossil abundance of Hole 29-284. 260 records from Range table from ostracoda in ODP Hole 144-873B. 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 4774 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 325 records from Planktic foraminifera abundance of Hole 32-305. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 2 records from A new genus and species of Laelapidae (Acari: Mesostigmata) from Iran. 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 2730 records from (Table 10) Distribution of planktonic foraminifera in the middle to late Miocene section of ODP Hole 149-900A. 85422 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 68077 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 2184 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 8523 records from Distribution of planktic foraminifers of core RC24-16. 336 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 186 records from Planktic foraminifera abundance of Hole 94-610. 6 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 1 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1346 records from Weevils of Poland. 4728 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 15 records from Kühnauer Aue und Kühnauer See. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 80 records from BB-Biodiversität b. 2 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 45 records from Antarctic Isopods. 4148 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 60 records from Planktic foraminifera abundance of Hole 19-192. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 7051 records from HRCB - Herbário Rioclarense. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 6 records from Microplankton counts and carbon biomass at station TT012_5-CTD35. 7 records from Analyses of the recent components of sediment core PS1219-1. 1312 records from GEO-Hauptveranstaltung (Insel Vilm). 239 records from Naturerlebnisraum Koppelsberg. 3 records from A new species of Auriculostoma (Trematoda: Allocreadiidae) from the intestine of Brycon guatemalensis (Characiformes: Bryconidae) from the Usumacinta River Basin, Mexico, based on morphology and 28 S rDNA sequences, with a key to species of the genus. 50 records from Planktic foraminifera abundance of Hole 60-457. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 2029 records from National Trust - Sutton Hoo species data held by The National Trust.. 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 27847 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 12142 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 879 records from Annotated list of observed birds in W and Pendjari Reserves in Benin, February 2010. 32 records from Ice Zooplankton Beaufort Sea. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_2-CTD16. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 111 records from Censo aéreo de poblaciones de borrego cimarrón (Ovis canadensis cremnobates) en Baja California, México. 491 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 77522 records from Avifauna de la Reserva de la Mariposa Monarca. 325 records from KU E16 Slæn - Tvinno. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 10 records from Review of amphipods of the Melita group (Amphipoda: Melitidae) from the coastal waters of Sakhalin Island (Far East of Russia). III. Genera Abludomelita Karaman, 1981 and Melita Leach, 1814. 233 records from Föhrenried (Fronreute und Baindt). 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 2 records from Neolinoptes gen. n., a replacement name for the net-winged beetle genus Linoptes Gorham, 1884 and a new species of Lycomorphon from Guyana (Coleoptera: Lycidae). 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 541 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 242 records from Biología del murciélago mastín enano (Eumops bonariensis nanus) en Yucatán. 820 records from Brood cell No. of trap-nesting species Alb 2008. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 77 records from Occurrence of recent nannoplankton in sediment core M1_MULT242, Arabian Sea (Fig. 2). 9 records from Coccolith counts of multinet M32/5_MSN982. 6869 records from UWBM Herpetology Collection (Arctos). 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 7 records from Nannofossil abundance of Hole 9-82A. 5 records from Nannofossil abundance of Hole 84-569. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 4138 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 4 records from Nannofossil abundance of Hole 52-418. 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 14 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 164 records from Planktic foraminifera abundance of Hole 94-610B. 314 records from Manual para la identificación de lianas en el campo. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 34 records from Order Araneae. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 233 records from Total foraminifera counts from M35/1_MSN1044. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 2478 records from (Figure 3) Range charts of selected dinoflagellate cysts in ODP Hole 122-762C. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 896 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 1562 records from Inventario de la vegetación acuática vascular de la reserva de la biosfera Pantanos de Centla, Tabasco. 40550 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 4710 records from Lyman Entomological Museum. 593 records from Ostracoda in sediment core PS51/159-10. 2539 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 354 records from Foraminifera distribution of sediment core KS310. 94 records from Planktic foraminifera abundance of Hole 32-310. 24 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 47 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 16 records from Abundance of radiolaria at station LV28-3-3. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 1379 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 14693 records from The Gordon Alexander Orthoptera Collection. 41 records from Altholzparzelle Eilenriede Hannover. 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 4 records from Review of the genus Chrysoscota in Cambodia (Lepidoptera, Erebidae, Arctiinae), with description of a new species. 20 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 125 records from Artenbestimmung. 10 records from Range table from planktonic foraminifers in ODP Hole 169-1038A. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 55 records from Galls on Beech Trees in Hainich, 2008. 3 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 308 records from Wangerooge. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 135 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 662 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 36 records from Occurrence of mammalia relicts at site Trebacki krs. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 135 records from Waldi-Weiher. 3 records from Sarcodine counts and carbon biomass at station TT011_15-CTD168. 1313 records from MCNH Museum of Cultural and Natural History Mammals Collection. 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 176153 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 1528 records from Inventario de los crustáceos decápodos asociados al ecosistema coralino de Pocillopora en el Pacífico tropical mexicano. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 56 records from Estetal (Buxtehude). 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 42 records from On the genus Trachysalambria Burkenroad, 1934 (Crustacea, Decapoda, Penaeidae), with descriptions of three new species. 42 records from BID-AF2015-0004-NAC - DENOMBREMENT SIMULTANE ET SYNCRONISE DES OISEAUX D’EAU MIGRATEURS AU TOGO. 224 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 133 records from Total foraminifera counts of multinet M21/3_MSN676. 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 149 records from Bayerische Donau - Neu Ulm. 32 records from Nannofossil abundance of Hole 67-499. 238 records from Coccoliths in ODP Hole 104-643A. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 2 records from Nannofossil abundance of Hole 7-64A. 92 records from Nottekanal, Klasse 7 - 10. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 34 records from Species of Wadicosa (Araneae, Lycosidae): transfer of two species from Pardosa and description of three new species from Africa. 14 records from Clasificación de tres especies endémicas de Mammillaria dentro del PROY-NOM-ECOL-059-2000. 4 records from Nannofossil abundance of Hole 16-156. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/466-2. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 35 records from Ortsrand Zandershagen. 410 records from (Appendix 3) Planktonic foraminiferal composition from ODP Site 172-1056. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 10596 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 143 records from Akita Prefectural Museum＋Malacostracans Specimens of Akita Prefectural Museum. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 32468 records from MedOBIS (EurOBIS). 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 3633 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 3 records from Nannofossil abundance of Hole 9-80. 2 records from Discovery of a New World ladybird beetle Nephaspis indus Gordon, 1996 (Coleoptera: Coccinellidae: Scymnini) on the Island of Taiwan. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 97 records from Occurrence of mammalia relicts at site Rejtek 1. 2984 records from USGS Marine Fishes of St. Croix and U.S. Virgin Islands. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 2 records from First record of Viannaiidae (Nematoda: Trichostrongylina) in fossorial rodents (Ctenomys spp.) from Central Argentina, with description of a new genus and species. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 316 records from Planktic foraminifera counts of sediment core RC11-86. 40 records from Tiere und Pflanzen um uns herum !. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 31 records from Nannofossil abundance of Hole 4-23. 23 records from Landwehrbach. 892 records from Weevils of Wales and England. 678 records from NCC Berkshire Chalk Grassland Survey 1985. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 296 records from (Appendix 1c) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber from MIS 11 of sediment core GeoTu_SL096. 3466 records from (Table 3) Distribution of benthic foraminifers at DSDP Hole 21-206. 36 records from Ice Algae Barents Sea. 29 records from Occurrence of mammalia relicts at site la Grotte du Thai. 26 records from SNH Invertebrate Site Condition Monitoring 2013/14: Loch Lubnaig Marshes SSSI. 58 records from Lüner Holz (Lüneburg). 8 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 19 records from (Table 1) Planktonic foraminifer abundance and stable isotope ratios of a sediment core near Baddeckenstedt, north Germany. 2321 records from CeDoc de Biodiversitat Vegetal: BCN-Phycophyta. 4935 records from UCM Bird Collection (Arctos). 38 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto75-83. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 15 records from Urwald 2 (Bad Waldsee). 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 5 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 12 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 388 records from SNH Invertebrate Site Condition Monitoring 2013/14: Ben Lomond SSSI. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 63 records from GenLink - Genetic diversity of Veronica chamaedrys. 7 records from Range table from planktonic foraminifers in ODP Hole 182-1132A. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 202 records from ZUEC-APL - Coleção de Aplacophora do Museu de Zoologia da UNICAMP. 3733 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 2 records from Revision of the coral-inhabiting genus Conopea (Cirripedia: Archaeobalanidae) with description of two new species of the genera Conopea and Acasta. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 353 records from Stadtgebiet (Dannenberg). 3 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 5 records from Fledermäuse u. nachtaktive Insekten. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 7034 records from Mollusca collection of National Museum of Nature and Science. 35832 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 181 records from Alien Species in Poland - Animals. 76 records from BIRDRACE Nachtigallen. 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 1294 records from MfN - Fossil vertebrates III. 10 records from Benthic macrofauna abundance of sediment core 12930-059. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 53 records from Programa regional para la caracterización y el monitoreo de ecosistemas de manglar del Golfo de México y Caribe Mexicano: Península de Yucatán. 2 records from Two new species of Bungona Harker, 1957 (Ephemeroptera: Baetidae) from Borneo, Indonesia. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 482 records from Kühmark bei Wetzlar. 68 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 2238 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 222 records from SNH Invertebrate Site Condition Monitoring 2013/14: Crathie Wood SSSI. 2 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 1297 records from Estudio taxonómico de las aves y mamíferos del Valle Cuatrociénegas, Coahuila, México. 89 records from Birdrace-Team_Wangerooge-Friesland. 28 records from Stadtpark Prinzengarten (Sigmaringen). 49 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_8-CTD102. 483 records from Artenvielfalt im Rhein-Neckar-Raum. 1812 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 20 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area II. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 100 records from Grenzturm Hohen Neuendorf. 180 records from Paul-Gerhardt-Schule Dassel. 269 records from BIRDRACE Dithmarscher Deichhühner. 122 records from Phytoplankton abundance at station CD46_1005C#4. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 525 records from Benthic foraminifera abundance of Hole 40-360. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 85 records from Sedimentological investigation on core V25-45. 10 records from Microzooplankton abundance and biomass at station TT043_21-22. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 7 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 47 records from Lepidurus arcticus survey Northeast Greenland 2013. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 531415 records from Swiss National Butterflies Databank. 48 records from Benthic foraminifera abundance of Hole 42-380A. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 185 records from Abundance of coccosphere-units of site GIK23414. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 1377 records from Red list project inventory, lichens. 2644 records from Invertebrates compiled by W.Block. 203 records from Planktic foraminifera abundance of Hole 72-515B. 707 records from Benthic foraminiferal assemblages of Upper Cretaceous sediments from DSDP Hole 74-527 in the Angola Basin, South Atlantic Ocean (Table I, Appendix II). 60 records from Schafsweide Seniorenhaus Berghof. 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 1236 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1208 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 10 records from A new species and new records of Hentzia (Araneae: Salticidae: Dendryphantinae) from the United States. 223320 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 222 records from Las tortugas marinas y sus playas de anidación en México. 1484 records from Base de datos de los pastos marinos mexicanos.. 3732 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10116 records from CUMV Mammal Collection (Arctos). 61 records from BIRDRACE Baumläufer. 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 7 records from Megafauna biomass in surface sediment during cruise PLG95A. 234 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 2. 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 3884 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 15 records from Eight new species of MacvIcarIa Gibson and Bray, 1982 (Digenea: Opecoelidae) mainly from endemic temperate marine fishes of Australia. 6 records from New Leucettidae de Laubenfels, 1936 (Porifera, Calcarea) from Western Australia. 567 records from Collection of Hymenoptera. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 4 records from Range table from nannofossils in ODP Hole 139-857A. 949 records from Determinación del estado de las poblaciones silvestres del cocodrilo de pantano (Crocodylus moreletii) en México y evaluación de su estatus en la CITES. 20 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 152 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 56 records from Zitadelle Berlin-Spandau (7b). 1657 records from Implementación del Programa de Monitoreo del Cocodrilo de Pantano (Crocodrylus moreletti) México-Belice-Guatemala en la Región de Coordinación MXRC3-Sur: sur de Veracruz, Tabasco, Chiapas y oeste de Campeche. 3489 records from Polish seed gene bank – historical passport data of accessions. 43 records from (Table 5) Distribution of calcareous nannofossils in DSDP Holes 92-600C and 92-601. 10 records from First description of the male of the spider Tibellus paraguensis Simon, 1897 (Araneae: Philodromidae), with new distribution records. 328 records from Diseño, planeación y manejo sustentable de ecoturismo. 12 records from Art´n Vielfalt im Kinderwald. 10 records from Zoobenthos in surface sediments during Professor Vodyanitskiy cruise PV32. 92 records from Nannofossil abundance of Hole 31-296. 31 records from Bayerische Donau - Tapfheim. 122 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 1015 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 7551382 records from BirdLife Australia, Birdata. 7470 records from National Taiwan University. 1243 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 102 records from Birdrace-OAG_Neuwerk-Hamburg. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 72 records from (Table 5) Distribution of nannofossils in DSDP Hole 87-583F. 14 records from Nannofossil abundance of Hole 14-140. 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 34 records from Catalogue of the type specimens of Bufonidae and Megophryidae (Amphibia: Anura) from research collections of the Zoological Institute, Russian Academy of Sciences. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 198 records from Total foraminifera counts from M35/1_MSN1047. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 81 records from Foraminifera species abundances from tow TT011_6-MOC65. 7 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 40 records from New taxa of Carpomyini, with special emphasis on Goniglossum (Diptera: Tephritidae: Trypetinae). 79 records from Umgebung von Schorndorf. 710 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 566 records from NRM-Herpetology. 20 records from Nannofossil abundance of Hole 7-63A. 7 records from Nannofossil abundance of Hole 27-259. 90 records from Planktic foraminifera counts of sediment core RC13-158. 704 records from Planktic foraminifera counts of sediment core V18-207. 1128 records from Southern Ocean Ostracoda (except Halocypridina). 429 records from Larval fish at Helgoland Roads in 2004. 1404 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part III. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 7811 records from Institut Botanic de Barcelona, BC-Histórico. 191 records from Foraminifera abundance of sediment core C1960.202. 1 records from Occurrence of mammalia relicts at site Ejstrup. 2630 records from Planktic foraminifera abundance of Hole 68-502A. 137 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 1046 records from (Appendix Table 4) Number of planktonic foraminiferal specimens within species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 786 records from Planktic foraminifera abundance of Hole 72-518. 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 59 records from Schulteich Freie Waldorfschule Darmstadt. 3953 records from Colección de Ostrácodos Recientes del Sur del Golfo de México (ICMyL-DF, UNAM). 63 records from Planktic foraminifera counts of sediment core V19-21. 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 21 records from (Figure 6) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-540. 2 records from Chaetognatha - SMF. 27 records from Pollen data of trap CB3. 797 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV23. 106 records from Arteninventar rund um den Rannahof. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 159 records from Total foraminifera counts of multinet SO118_MSN1251. 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 492 records from Pliocene/Pleistocene benthic foraminiferal abundances from hole KR9912PC4. 173 records from (Table T3) Stable isotope ratios and abundances of foraminifera from ODP Hole 172-1063D. 638 records from Geochemistry and sedimentology on core PO200/10_21-1. 446 records from Bayerische Donau - Blindheim Donaubrücke. 5 records from Analyses of the recent components of sediment core PS1216-1. 27 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 468 records from Range table from planktonic foraminifers in ODP Hole 155-932A. 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 35 records from Range table from planktonic foraminifers in ODP Hole 180-1112A. 6816 records from English Nature Oxfordshire Invertebrate Surveys. 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 10 records from (Figure 9) Relative abundance of nannoliths at DSDP Hole 62-465A. 1641 records from Arácnidos de Centroamérica. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 124 records from Range table from benthic foraminifers in ODP Hole 189-1171A. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 10 records from Oberservation of birds at station PS14/143 along 49° West. 2959 records from Biological observations from the Dana Expedition Reports. 226 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 71 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 23 records from (Table 3) Neogene relative abundances of Uvigerina spp. at DSDP Hole 95-613. 112 records from Implementación del programa de monitoreo del cocodrilo del pantano (Crocodylus moreletti) México-Belice-Guatemala: región de coordinación MXRC2-Golfo Centro, Veracruz centro y norte Oaxaca [Temporada 2013]. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 2 records from Hyphessobrycon petricolus, a new species of tetra (Characiformes: Characidae) from the rio Madeira basin, Mato Grosso, Brazil. 2 records from Duocrassana longula, new genus and species of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae) from southern Mexico and its relationship to other genera in Athysanini. 2 records from Nannofossil abundance of Hole 18-174A. 288 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 181 records from Nematode abundance of the Eastern Mediterranean Sea in cold seep sediments collected during MSM13/3 and MSM 13/4 cruises (2009). 54 records from Biotope im Schulumfeld. 232 records from Distribution of planktic foraminifera of sediment trap OG5. 7924 records from Dinoflagellate cysts in surface sediments. 18750 records from National Trust - Hatfield Forest species data held by The National Trust.. 13 records from Benthic macrofauna abundance of sediment core 12930-065. 12 records from Nannofossil abundance of Hole 74-528A. 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 4 records from Zwischen Enz und Schule. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 3 records from Planktic foraminifera abundance of Hole 54-419. 1 records from Distribution of haploniscids (Isopoda, Asellota, Haploniscidae) in Icelandic waters, with description of Haploniscus astraphes n. sp. from the Iceland basin and the Southeast Atlantic Ocean. 142 records from Ostracoda in sediment core PS51/135-4. 137 records from Corvids Literature Database. 884 records from Percentages of planktonic foraminifera species in sediment core EN066-10PG. 1137 records from Planktic foraminifera abundance of Hole 72-516F. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 132439 records from HBRG Insects Dataset. 19 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-139BX. 1013 records from Planktic foraminifera counts of sediment core RE5-034. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 1999 records from Composición florística y estructura de una parcela permanente en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 3 records from Sarcodine counts and carbon biomass at station TT007_3-CTD29. 1 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 33 records from Kirkegaardia (Polychaeta, Cirratulidae), new name for Monticellina Laubier, preoccupied in the Rhabdocoela, together with new records and descriptions of eight previously known and sixteen new species from the Atlantic, Pacific, and Southern Oceans. 61002 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 873 records from Kartlegging av spredning av fremmede bartrær. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 57 records from Schulgarten Fichteschule. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 44 records from Total foraminifera counts of multinet M27/2_MSN879. 27 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5121-1. 22 records from Phytoplankton abundance at bottle station GOM1/6. 18 records from Smear slide analysis on sediment core GeoB4206-1. 137 records from Planktic foraminifera counts of sediment core V28-25. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 264 records from Planktic foraminifera counts of sediment core RC12-339. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 7341 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 17 records from Coccoliths in sediment core PS1527-2. 185 records from (Table 2) Abundances of dinoflagellates in ODP Hole 105-646B. 8 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 18247 records from Actualización de la base de datos sobre la flora de la Reserva de la Biósfera Sierra de Manantlán, Jalisco-Colima, México. 8933 records from National Invasive Species Database. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 8 records from Nannofossil abundance of Hole 49-412A. 181 records from (Table 3) Range chart of calcareous nannofossils in ODP Hole 122-763B. 1 records from Description of lithologic section units of IODP Hole 325-M0052C. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 39 records from Calcareous dinocysts along profile Ruegen. 3 records from Sarcodine counts and carbon biomass at station TT011_9-CTD115. 171 records from Sahrbachtal Kreis Ahrweiler. 14 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT243, Arabian Sea (Fig. 2). 4 records from Nannofossil abundance of Hole 55-430A. 22 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 15 records from Biodiversidad microbiana de los ecosistemas marinos en la Isla Cayo Serrana durante la Expedición Seaflower 2016. 23 records from AlgaTerraMovies. 376 records from Wupperaue bei Kemna (Wuppertal). 327 records from Foraminifera abundance of Hole 58-443. 6 records from Scolopendromorpha of New Guinea and adjacent islands (Myriapoda, Chilopoda). 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 5 records from Occurrence of mammalia relicts at site Victoria Cave. 347 records from Planktic foraminifera abundance of Hole 21-209. 500 records from Foraminifera abundance of Hole 48-404. 3763 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 1571 records from Diptera, NEF. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 57 records from Kindervilla Aussengelände/ Hiltroper Park. 410 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part II. 111 records from Genética y taxonomía de los robalos (Centropomus spp) del golfo de California, México. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 1059 records from Planktic foraminifera abundance of Hole 15-148. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 651 records from Range table from planktonic foraminifers in ODP Hole 155-940A. 349 records from Range table from planktonic foraminifers in ODP Hole 182-1126B. 3 records from Dinoflagellate abundance of Hole 85-572. 15733 records from imr_mareano_beamtrawl. 88 records from Total foraminifera counts of trap L2_92_A43. 214 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano y Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 2320 records from (Table 7) Distribution of planktonic foraminifera in the early Miocene to late Pliocene section of ODP Hole 149-899A. 465 records from Philosophenwald und Wieseckaue in Gießen. 145 records from Microplankton abundance in the euphotic zone of the Levantine Sea in October-November 1991. 751 records from Planktic foraminifera abundance of Hole 49-408. 23 records from Benthic foraminifera abundance of Hole 93-603. 62 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 65079 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 2036 records from Caracterización biológica de la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 19 records from MVZ Herp Observations (Arctos). 1226 records from M. Andrew Johnston Collection. 160 records from Total foraminifera counts of multinet M21/1_MSN607. 19 records from Pollen record from Mamontovy Klyk. 6861 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 479 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P5. 13 records from Foraminifera abundance of Hole 57-438B. 1 records from A new species of Diastatotropis Lacordaire (Coleoptera: Anthribidae) from Montagne d’Ambre National Park, northern Madagascar. 49 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 804 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 2 records from Two new species of Chromadoridae (Chromadorida: Nematoda) from the East China Sea. 44 records from Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean). 6242 records from Natural history museum data on Canadian Arctic marine benthos. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN658. 765 records from Reptiles and Amphibians Distribution Atlas 1978 (An Foras Forbartha). 17 records from Abyssal fauna of the UK-1 polymetallic nodule exploration area, Clarion-Clipperton Zone, central Pacific Ocean: Cnidaria. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_240-4. 9955 records from Benthic foraminifera abundance in counts of Hole PRAD1-2. 101 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 2 records from New species of Pseudachorutes (Collembola: Neanuridae) from Northeastern Algeria. 1763 records from Arachnida of Costa Rica (INBio). 1189 records from Saproxylic insects caught in window traps and hatched from polypores in small and large old forests in southern Norway. 17640 records from UFP - Herbário UFP - Geraldo Mariz. 506 records from Nemátodos acuáticos de vida libre de Quintana Roo. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 84 records from BIRDRACE Avinauten. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 95 records from Total foraminifera counts from multinet M31/2_MSN896. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 28 records from (Table A) Wet weight night biomass of dominant mesozooplankton groups obtained from night catches within the Bismark Polygon in June 2001 and June-August 2002. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 1017 records from Planktic foraminifera abundance of Hole 26-253. 59 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 188 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 279 records from Koleopterologen am Bausenberg. 40 records from (Table T1) Kerogen and organic constituents in ODP Hole 183-1138A, Kerguelen Plateau. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 526 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-17-7. 5960 records from Recuento de la diversidad florística de Veracruz. 16232 records from Birds Specimens. 475 records from Herp specimens. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 3669 records from ARKO strandeng. 80 records from Total foraminifera counts of multinet M12/3_MSN543. 2912 records from The Erysiphales Collection at the University Halle-Wittenberg. 137 records from Planktic foraminifera counts at CTD station PS55/077-1. 521 records from Bayerische Donau - Leipheim. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD85. 2 records from Nannofossil abundance of Hole 10-87. 12256 records from Hongos del estado de Veracruz. 14 records from Description of lithologic section units of IODP Hole 325-M0047A. 8064 records from Vascular Plants Collection of Sagamihara City Museum. 2072 records from Coleópteros malacodermos (Phengodidae, Cantharidae, Lycidae, Lampyridae) del estado de Veracruz, México. 41915 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 321 records from Fuldaaue (Stadtgebiet Fulda). 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 876 records from Range table from planktonic foraminifers in ODP Hole 138-847B. 133 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 3786 records from Faun. 983 records from (Table 2) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-747A. 18 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part I. 1973 records from Biodiversidad de crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas (R53, Río San Juan y Río Pesqueria). 1322 records from Taxonomía y sistemática de la Ictiofauna de la Bahía de Banderas del Estado de Nayarit, México. 5497 records from Anfibios y reptiles del estado de Querétaro. 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 73 records from Tiergarten (Zeitz). 1 records from Occurrence of mammalia relicts at site Egtved. 5 records from Range table from planktonic foraminifers in ODP Hole 178-1103A. 471 records from Los peces del área oaxaqueña de la Reserva de la Biosfera Tehuacán-Cuicatlán. 1742 records from Eggs Specimen. 221 records from Foraminifera abundance of sediment core IN68-5. 35 records from Range table from planktonic foraminifers in ODP Hole 144-873A. 1131 records from (Appendix A1) Abundances of planktonic and benthic foraminifera in the Turonian to Coniacian sediments of ODP Site 207-1259. 315 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 1500 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Day/night stratified zooplankton sampling onboard the Norwegian R/V Jan Mayen. Program ALV. 14 records from Plasm bearing foraminifera counts from multinet M31/2_MSN893. 41 records from (Table 3a) Distribution of planktonic foraminiferal tests in sediments from Core NKA-37T. 260 records from Tejidos colectados en la ventana de biodiversidad Ciénaga, Municipio de Ciénaga, Magdalena, Colombia. 2213 records from JOI - Herbário Joinvillea. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 3330 records from Collection botanique Le Grand A. (BOUM). 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 12 records from Distribution of meiobenthos in sediment core M19_229-2 of the northeastern Atlantic (Table 1). 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 58 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 7900 records from English Nature Oxfordshire Chalk Grassland Survey. 46 records from Phytoplankton abundance at bottle station A9/5. 11737 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 691 records from Ocurrencia, distribución y abundancia del género Passerina en la Reserva de la biosfera La Sepultura, Chiapas. 88 records from (Figure 5) Distribution and relative abundances of microbiota recovered from the Jurassic section of DSDP Hole 79-547B. 2 records from Taxonomic status of the family Biokoviellidae Mršić, 1992 (Diplopoda, Chordeumatida): reconsideration, with a description of one new species. 2 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 1655 records from Florida Keys Reef Visual Census 1995. 2 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 90 records from Plasm bearing foraminifera counts of multinet M21/2_MSN639. 1576 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv).. 115 records from Total foraminifera counts of multinet PO247/2_MSN1382. 89 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 1120 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 103 records from Birdrace-Die_Nachtigallen-Herford. 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 22854 records from R. L. McGregor Herbarium Lichen Collection. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 4719 records from IBF Monitoring of Lichens. 10 records from Propagación y manejo productivo de poblaciones de Mellipona beecheii. 7 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 160 records from (Table 1b) Relative percent abundance of planktic foraminiferal species at DSDP Site 77-536, Late Cretaceous. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 94 records from Total foraminifera counts of multinet M21/4_MSN697. 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 9 records from Phytoplankton abundance at station Casma_2003-06-04_2, Casma, Peru. 121 records from Relative abundance of radiolaria in surface sediments. 2 records from Nannofossil abundance of Hole 74-525A. 1848 records from (Table 3) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 5 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 628 records from Relative abundance of planktic foraminifera in sediment core TR126-29 from the 120 kyr time slice reconstruction. 1527 records from Diversidad de orquídeas en la región El Momón-Margaritas-Montebello, Chiapas, México. 6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 1360 records from (Appendix table DR1) Foraminiferal distribution data for ODP Hole 178-1098B. 34 records from Relative abundance of coccosphere-units of sediment core GIK23071-3. 2 records from Nannofossil abundance of Hole 66-488. 72 records from Occurrence of nannoplankton observed in Early Pliocene samples from Zanclean stratotype of Capo Rossello, Sicily (Table I). 130 records from Planktic foraminifera counts of sediment core RC11-120. 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 8 records from Component analysis of TV-guided grab sampler GeoB10071-4. 325 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 115-708A. 6880 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 13 records from CNAN/Pseudoscorpiones. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_8-CTD102. 262 records from Coiling ratios of Pulleniatina spp. in sediments from DSDP Hole 16-157. 338 records from ConDidact Citizen Science Surveys - Snails 2012. 407 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 214 records from Planktic foraminifera counts of sediment core V27-86. 6723 records from NOAA HML Tidal Creek Database. 54856 records from Colección de Referencia de Lepidópteros Diurnos Mexicanos de la CNIN (Lepidoptera: Papilionoidea) (IBUNAM). 51 records from Taxonomic revision of the spider family Penestomidae (Araneae, Entelegynae). 24 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB02 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 354 records from Microfossil abundance of Hole 35-323. 14 records from Range table from benthic foraminifers in ODP Hole 178-1101A. 1 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 6229 records from (Table 9) Percentages of planktonic foraminiferal taxa from Site GIK17940. 81 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB6. 2 records from Occurrence of mammalia relicts at site Condover. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 11 records from Oberservation of birds at station PS14/145 along 49° West. 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 11303 records from NCSM Mammals Collection. 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 1 records from Eidinemacheilus, a new generic name for Noemacheilus smithi Greenwood (Teleostei; Nemacheilidae). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 4251 records from Aves de la cuenca media del río Chambery, Caldas. 6566 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-112BX. 3027 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 3 records from Akita Prefectural Museum＋Echiurans Specimens of Akita Prefectural Museum. 5924 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 75 records from Abundance of microzooplankton measured on water bottle samples during POLARSTERN cruise ANT-X/6. 3 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 4 records from A new species of Hyphessobrycon Durbin (Characiformes: Characidae) from rio Aripuanã, rio Madeira basin, Brazil. 2059 records from (Table 22) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-594. 301 records from Modelación de la distribución geográfica de las especies del género Abies presentes en México. 4282 records from Universitat de Girona: HGI-Cormophyta. 72 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 400 records from Distribution of planktonic foraminifera in Oligocene-Miocene of three drill sites from the netherlands Peel area. 1153 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 4007 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 3939 records from Census of plant species in Pahou forest reserve. 57376 records from Records from the NIWA AllSeaBio marine biology database. 3270 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en el Complejo de Páramos Perijá. 10465 records from Monitoreo complementarios de algas, invertebrados y peces en el Parque Nacional Arrecifes de Cozumel. 179061 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 3695 records from Distribution of planktic foraminifera in ODP Site 202-1240 samples. 155 records from Total foraminifera counts of multinet M10/2_MSN231. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 8 records from Planktic foraminifera abundance of Hole 29-278A. 187078 records from Geneva Herbarium – General Collection (G). 4498 records from Colección Herbario Universidad Católica de Oriente. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 213 records from Colección nacional de palmas de Colombia - JBQ. 1 records from New sighting of the endangered species blackchin guitarfish, Rhinobatos cemiculus, in the South Aegean Sea. 780 records from Comportamiento espacio-temporal de la densidad fitoplanctónica en el año 2015 Magdalena, Colombia. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 204 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB1710-3. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 21 records from Vogelwelt im Europa-Rosarium. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 194 records from Bodenteicher Seewiesen. 11 records from Microzooplankton abundance and biomass at station TT050_21-13. 16 records from Nannofossil abundance of Hole 24-235. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 23 records from 2. Aspacher GEO-Tag der Artenvielfalt. 10 records from (Table 3) Minerals and components of sediments from DSDP Site 94-609_Site, North Atlantic. 588988 records from Danish Mycological Society, fungal records database. 7 records from Analyses of the recent components of sediment core PS1219-1. 710 records from Evaluación del impacto de una especie íctica invasora Cyprinus carpio en el Lago de Pátzcuaro, Michoacán. 10966 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 574 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 4967 records from SANT Herbarium vascular plants collection. 14 records from Nannofossil abundance of Hole 94-611A. 8634 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 18 records from Occu
Keywords: GBIF; biodiversity; species occurrences